Pendampingan implementasi kurikulum merdeka melalui modul ajar berbasis proyek lingkungan lahan basah - Yulinda, Ratna; Khairunnisa, Yasmine; Sauqina, Sauqina; Hafizah, Ellyna; Sari, Mella Mutika; Syaban, M. Fuad (STAI Auliaurrasyidin Tembilahan, 2024)
This community service activity was motivated by the challenges faced by partner educators, including limited skills in using science teaching kits (KIT IPA) and difficulties in finding alternative simple teaching tools. These issues hinder innovation in science education at the MTs level. The objectives of this program were: 1) to provide information on the implementation of the Merdeka Curriculum (IKM) and project-based learning, 2) to develop teaching modules and student worksheets (LKPD) based on wetland environment projects, and 3) to demonstrate project-based learning methods. The methods employed included socialization, training, mentoring, evaluation, and sustainability planning. The results showed that teachers gained an understanding of the Merdeka Curriculum implementation, were able to develop project-based teaching modules and LKPD and received practical examples of project-based learning. This program supports MTs science teacher working groups (MGMP) in implementing the Merdeka Curriculum, utilizing KIT IPA, and employing simple tools for project-based environmental learning.